The Role of Parental Mediation on Children's Sustained Attention in Short Video Exposure - Tita Sapriyanti; Arnita Fitri; Thea Yuliana Anjari; Aisyah Oktavia Siregar; Ribi Annisa Karimah (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has increased young children's exposure to short-form video content. Fast-paced visual characteristics (fast visual content) are assumed to influence children's cognitive abilities, particularly sustained attention. However, the role of parental mediation in moderating this relationship remains underexplored. This study aims to analyze the effect of short-form video exposure intensity on sustained attention among children aged 5–6 years and to examine the moderating role of parental mediation. A quantitative approach with a correlational survey design was employed involving 21 children and their parents (n = 21). The instruments included scales of video exposure intensity, sustained attention, and parental mediation. Data were analyzed using linear regression and Moderated Regression Analysis (MRA). The findings reveal that the intensity of short-form video exposure has a significant negative effect on children's sustained attention (β = -0.45; p 0.05). Furthermore, parental mediation significantly moderates this relationship (β = 0.30; p 0.05), indicating that parental involvement weakens the negative impact of digital media exposure. These results highlight the importance of active parental involvement as a protective factor in early childhood cognitive development. Therefore, strengthening parental mediation strategies is essential in addressing the challenges of digital media use among young children.